Pendidikan Islam Wasathiyah ke-Indonesia-an - Amar , Abu (LPPPM STAI Darul Hikmah Bangkalan, 2018)
Wasathiyah or moderate Islamic education is a planned and systematic effort to bring the learner to the middle, not to exaggerate in a particular position, to be at the point of attitude perpendicular to the truth or to uphold justice. In the implementation of moderate personality has the understanding and practice of religion with the characteristics: moderation, balance. straight and firm, tolerant, egalitarian, deliberative, reformist and inhospitable.The focus of this paper would be to elaborate the extent of tolerance as the most important feature of wasathiyah Islam being the goal